Genomic surveillance reveals the detection of SARS‐CoV‐2 delta, beta, and gamma VOCs during the third wave in Pakistan. Issue 3 (9th November 2021) - Umair, Massab; Ikram, Aamer; Salman, Muhammad; Haider, Syed Adnan; Badar, Nazish; Rehman, Zaira; Ammar, Muhammad; Rana, Muhammad Suleman; Ali, Qasim
Abstract: SARS‐CoV‐2 variants of concern (VOCs) have emerged worldwide and gained significant importance due to their high transmissibility and global spread, thus meriting close monitoring. In Pakistan, limited information is available on circulation of these variants as the alpha variant has been reported the main circulating lineage. The current study was designed to detect and explore the genomic diversity of SARS‐CoV‐2 lineages circulating during the third wave of the pandemic in the indigenous population. From May 01 to June 09, 2021, a total of 16 689 samples were tested using TaqPath™ COVID‐19 kit for the presence of SARS‐CoV‐2. Overall, 2562 samples (15.4%) were COVID‐19 positive. Out of these positive samples, 2124 (12.7%) did not show the spike gene amplification (spike gene target failure ([SGTF]), whereas 438 (2.6%) showed spike gene amplification (non‐SGTF). A subset ( n = 58/438) of non‐SGTF samples were randomly selected for whole‐genome sequencing. Among VOCs, 45% ( n = 26/58) were delta, 46% ( n = 27/58) were beta, and one was gamma variant. The delta variant cases were reported mainly from Islamabad ( n = 15; 58%) followed by Rawalpindi and Azad Kashmir ( n = 1; 4% each). Beta variant cases originated mainly from Karachi ( n = 8; 30%) and Islamabad ( n = 11; 41%) and the gamma variant case was reported in a traveler from Italy. The delta, beta, and gamma variants possessed lineage‐specific spike mutations. Notably, two rare mutations (E484Q and L5F) were found in the delta variant. Furthermore, in the beta variant, two significant rare non‐synonymous spike mutations (A879S and K444R) were also reported. High prevalence of beta and delta variants in local population may increase the number of cases in the near future and provides an early warning to national health authorities to take timely decisions and devise suitable interventions to contain a possible fourth wave.